Performance of Exotic Poplar Clones in Tarai (Uttar Pradesh) - Chandra, J. P.; Joshi, B. C. (Indian Forester, 1994)
Six years growth of performance trial of 32 clones of poplar growing under agro-climatic conditions of Tarai are reported. Object of the study was to locate clones other than G-3 and G-48 for commercial cultivation. Clone S7C4, S7C8, S7C15 and S7C20 were observed to be growing equally well and all of them are so far immune to leaf blight disease caused by Bipolaris maydis. Planting of intimate mixture clone G-3, G-48,S7C4, S7C8, S7C15 and S7C20 is advocated for commercial plantations.